Making Capital Markets Work For Africa: Interrogating Progress, Challenges and the Pursuit Of Integration - Nambatya, Prosscovia (Trinity College Dublin. School of Law. Discipline of Law, 2022)
The work which follows examines the foundation, state, and practice of stock market integration projects in Africa which are fronted as a solution to making capital markets work for Africa. There is a consensus that African capital markets face immense challenges, and the research identifies the impediments hindering the development of the markets. Principally these include illiquidity, low levels of market activity including limited initial public offers, low trading volumes and transactions, limited cross border activity, inadequate securities regulatory frameworks, unfavourable macro-economic and fiscal policy, and inadequate and inefficient market infrastructure. The thesis provides evidence and statistics to quantify the magnitude of the challenges facing African stock markets. In the search for solutions to overcome these challenges, regulators, policy makers and political leaders have advanced integration as a viable solution. Integration has its origins in the post-colonial times and the calls for a unified Africa through the various post-independence treaties at both AU and regional level. This thesis examines the concept of regionalism and the formation of regional economic communities (RECs) as the conduits of integration and as the proponents of the multimillion-dollar stock market integration projects in Africa. The thesis interrogates the challenges that the legal challenges that these integration projects have faced. Principally these are either foundational or operational challenges. Foundational challenges, for example include the threat to the existence of the national exchange and the sovereignty concerns that this raises as well as the lack of a financing mechanism and the limited understanding of the concept of an economic community. Operational challenges include multiple memberships to the RECs and the complex interaction between regional and national law and the lack of a dedicated judicial body and monitoring mechanisms. The work proposes solutions to each of these. The work then examines the concept of regulatory harmonisation as an alternative proposal to stock market integration.
APPROVED
Keywords: Integration; Regulatory Harmonisation; Regionalism; Capital Markets